Identification of three prominin homologs and characterization of their messenger RNA expression in Xenopus laevis tissues - Han, Zhou (Molecular Vision, 2011)
PURPOSE: Prominin is a family of pentaspan transmembrane glycoproteins. They are expressed in various types of cells, including many stem/progenitor cells. Prominin-1 plays an important role in generating and maintaining the structure of the photoreceptors. In this study, we identified three prominin homologs in Xenopus laevis, a model animal widely used in vision research, and characterized their messenger RNA (mRNA) expression in selected tissues of this frog. METHODS: Reverse-transcription PCR (RT–PCR) and rapid amplification of cDNA ends (RACE) were used to isolate cDNAs of prominin homologs. Semiquantitative RT–PCR was used to measure the relative expression levels of mRNAs of the three prominin homologs in four X. laevis tissues, specifically those of the retina, brain, testis, and kidney. Sequences of prominin homologs were analyzed with bioinformatic software. RESULTS: We isolated cDNAs of three prominin homologs from X. laevis tissues and compared their sequences with previously described prominin-1, 2, and 3 sequences from other species using phylogenetic analysis. Two of these homologs are likely to be the X. laevis orthologs of mammalian prominin-1 and 2, respectively, while the third homolog is likely to be the X. laevis ortholog of prominin-3, which was only found in nonmammalian vertebrates and the platypus. We identified alternatively spliced exons in mRNAs of all three prominin homologs. Similar to mammalian prominin-1, we found that exons 26b, 27, and 28a of the X. laevis prominin-1 gene are alternatively spliced, and that the splice isoforms of mRNA show tissue-specific expression profiles. We found that prominin-1 was the most abundant homolog expressed in the retina, brain, and testis, while prominin-3 was the most abundant homolog in the kidney. The expression level of prominin-2 was the lowest of the three prominin homologs in all four examined tissues of this frog. CONCLUSIONS: Our results suggest that the mRNAs of prominin homologs are expressed in many tissues of X. laevis, but differ in their expression levels and mRNA splicing. Prominin-1 is the most abundant of the three prominin homologs expressed in the frog retina.